PENGARUH AKUNTABILITAS, TRANSPARANSI DAN KETEPATAN WAKTU TERHADAP KINERJA ANGGARAN (Studi Empiris Pada Organisaasi Perangkat Daerah Kota Pekanbaru) - Prasetyo Prasetyo; Kennedy Kennedy; Kurnia Pipin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of accountability, transparency, and timeliness on budget performance at OPD in Pekanbaru City. The population is all OPD in Pekanbaru City. The sampling technique used purposive sampling method with a total sample of 81 subjects. The data collection technique used in this research is a questionnaire. The data analysis technique used is multiple regression. The results showed that the variables of accountability (X1) has a positive effect on the performance of the budget, with a value oftcount > 4.142 ttable 1.991 or sig 0.000 < 0.05. Variable transparency (X2) has a positive effect on the performance of the budget withtvaluethe 2,551 > ttable 1.991 or sig of 0.013 < 0.05 so. Variable timing (X3) effect on the performance of the budget, with a value oft > 2,215 ttable 1.991 or sig of 0.030 < 0.05.Keyword : Akuntabilitas, Transparansi dan Ketepatan Waktu terhadap Kinerja Anggaran